Pengembangan profesionalisme guru madrasah ibtidaiyah melalui workshop, supervisi, dan komunitas belajar - Naila, Dzurrotun (Maliki Interdisciplinary Journal, 2026)
Teacher professionalism is a key determinant of the quality of education, including in Islamic Elementary Schools (MI). The current low level of professionalism among MI teachers negatively impacts the quality of learning and public trust in madrasas. This literature-based research aims to analyze strategies for developing structured and sustainable MI teacher professionalism through three approaches: workshops, academic supervision, and learning communities. The study results indicate that workshops effectively improve practical skills (curriculum, planning, classroom management, and modern media/methods). Academic supervision provides constructive and objective guidance. Meanwhile, learning communities (MGMP, KKG, literacy, digital) facilitate collaboration, exchange of good practices, and development of innovations. In conclusion, the integration of these three strategies has been shown to contribute significantly to strengthening the four teacher competencies (pedagogical, professional, social, and personality), thereby ensuring more optimal and sustainable improvement in MI teacher professionalism with adequate institutional support.